(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Online shopping has become a recent phenomenon in the field of electronic business and has gained familiarity among consumers around the world. Most of the companies are now adopting online portals to sell their products/services online. Though in countries like India, the trend of online shopping took some time to develop, but now a days, there is a craze for online shopping both among the younger and elderly populations. Compared to traditional store shopping, online shopping has received much more attention. The purpose of this study is to determine the driving factors affecting the online buying behavior of consumers and to analyze the impact of these driving factors on online buying intentions. To meet the research objectives, multiple regression analysis has been applied. The results of the study revealed that in order of their impact size, the most significant predictors of online buying behavior are convenience, impulse buying behavior, congruence, shopping enjoyment, browsing enjoyment, value consciousness, price consciousness and risk. The research provides a novel finding of the strongest effect of impulse buying behavior, which has not previously been identified as a key antecedent to online shopping.